All the way [videorecording (DVD)] - Cranston, Bryan, 1956-; Leo, Melissa; Whitford, Bradley; Mackie, Anthony, 1978-; Langella, Frank (HBO Home Box Office, 2016)
Bryan Cranston stars in a riveting look at the formidable challenges and demons faced by President Lyndon Johnson on his tumultuous first year in office, from his accidental ascension to the presidency in November 1963, to his relentless fight to win passage of a landmark Civil Rights Bill with the election of 1964 looming.